Cognition and Estrangement in Two Recent Argentinian Novels - Feuillet, Lucía (Universidad Pedagógica y Tecnológica de Colombia, 2023)
We propose a study of cognition ways constructed from the category of estrangement in the science fiction novels V (2017), by Mariana Docampo, and El ojo y la flor (2019), by Claudia Aboaf. Marxism and Cultural Interpretation are taking into account through Fredric Jameson contributions. This approach focuses on read the relationship between subjective experiences and a fragmented and conflictive social totality that are suggested in the storytelling atmospheres. The reading of those novels is oriented around estrangement technique in both the enunciation and the plot. In any case, the novels aesthetic proposal exhibits the construction of an alternative epistemology which moves from the recognition of contradictions towards the configuration of unexpected associative networks.